Spontaneous pneumothorax due to recently diagnosed active pulmonary tuberculosis - Carrillo, Leonidas (2010)
We describe the case of a male patient aged 17, Lima student who had no history of known tuberculosis contact, nonreactive HIV ELISA, diagnosed 21 days befote admission with active pulmonary tuberculosis, sputum smear 3 +, who was started with first line antituberculosis drugs. He was admitted to the hospital for pleural chest pain of sudden onset, and moderate dyspnea; on physical examination there was abolition of vocal vibrations, absence of breath sounds and hyperresonance in right hemithorax, compatible with pneumothorax on that side. Chest radiograph showed significant pulmonary collapse in the right hemithorax. Chest tube and water seal drainage were placed and he continued specific treatment for pulmonary tuberculosis. He had a torpid evolution, complicated by pyogenic empyema requiring thoracostomy with prolonged hospitalization. Spontaneous pneumothorax due to newly diagnosed active pulmonary tuberculosis is a rare complication, which motivates this presentation.